The Association between Non- Enzymatic Dietary Total Antioxidant Capacity and Phytochemical Index with Semen Parameters: A Cross-Sectional Study in Isfahan Infertile Men - Masha Shirani; Zohreh Ghaem Far; Milad Bagheri; Mehran Nouri (Journal of Nutrition and Food Security, 2022)
Background: Infertility affects about 15% of the population and male factors only are responsible for ~25–30% of cases of infertility. Oxidative stress is an imbalance between the production of free radicals and the capacity of the body to counteract their harmful effects through neutralization by antioxidants. This study aims to access the relationship between non-enzymatic dietary antioxidant capacity and male infertility. Methods: In this cross-sectional study, 270 infertile men aged 18-55 years were selected from Isfahan province in 2018. Semen assessment was performed according to the fifth edition of the WHO laboratory manual and a 168-item food frequency questionnaire (FFQ) questionnaire was used to determine the amount of dietary intakes of participants. P-value < 0.05 was considered statistically significant. Results: There were no significant association between sperm parameters and dietary total antioxidant capacity (DTAC) tertiles in the crude model and after adjustment for potential confounders. The participants in the highest tertile of DTAC had a higher risk of abnormal density and motility in crude model (OR=1.30; 95% CI: 0.65, 2.59; P = 0.46 and OR=1.69; 95% CI: 0.83, 3.44; P = 0.99) and risk of abnormal density decreased in the adjusted model (OR=0.99; 95% CI: 0.39, 2.50; P = 0.99) and (OR: 1.43; 95% CI: 0.51, 4.01; P = 0.5). Conclusion: In this cross-sectional study there was no significant relationship between semen parameters and DTAC tertiles in the crude and adjusted model. Therefore, it is required to conduct more research studies to determine the clear benefits and risks of antioxidant therapy for infertility.